PENGARUH LINGKUNGAN BELAJAR MANDIRI DAN PEMBELAJARAN DARING TERHADAP PRESTASI AKADEMIK SELAMA PANDEMIK KELAS VIII SMP SWASTA YOSEF ARNOLDI BAGAN BATU - Dearlina Sinaga; Sthepanie Turnip; Christine Haray Naibaho (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
This study aims to determine the effect of the independent learning environment and online learning on academic achievement during the pandemic of class VIII Yosef Arnoldi Bagan Batu Private junior High School in social studies subjects for the 2021/2022 academic year. Quantitative research approach with survey method, the population off all class totaling 68 students as research sample. The analitycal method used is multiple linear regression analysis. Data analysis techniques used in this study include partial t-test, simultaneous hypothesis (F-test) and determination coefficient (R2). The results showed that the independent learning environment and online learning had a positive achievement with the equation Y=1,607 + 0,629 X1 + 0,409X2. Partial hypothesis testing for the X1 variable obtained t-count X1(5,825) > t-table (1,98) which can be concluded that independent learning environment has a significant effect on a academic and variable X2 is obtained t-count X2 (5,741) > t-table (1,98) which can be concluded that online learning has a significant effect on academic achievement. The coefficient determinant test (R2) shows that the adjusted r-square = 0,618, meaning that 61,8 % of academic achievement is influenced by independent learing and online learning variables, while the rest (38,2%) is explained by other factors.Keywords: Independent Learning Environment; Online Learning; Academic Achievement